Cell therapeutic approaches to immunosuppression after clinical kidney transplantation - Morath, Christian; Schmitt, Anita; Kälble, Florian; Zeier, Martin; Schmitt, Michael; Şandra-Petrescu, Flavius Ionuţ; Opelz, Gerhard; Terness, Peter; Schaier, Matthias; Kleist, Christian (Pediatric nephrology, 2018)
Refinement of immunosuppressive strategies has led to further improvement of kidney graft survival in recent years. Currently, the main limitations to long-term graft survival are life-threatening side effects of immunosuppression and chronic allograft injury, emphasizing the need for innovative immunosuppressive regimens that resolve this therapeutic dilemma. Several cell therapeutic approaches to immunosuppression and donor-specific unresponsiveness have been tested in early phase I and phase II clinical trials in kidney transplantation. The aim of this overview is to summarize current cell therapeutic approaches to immunosuppression in clinical kidney transplantation with a focus on myeloid suppressor cell therapy by mitomycin C-induced cells (MICs). MICs show great promise as a therapeutic agent to achieve the rapid and durable establishment of donor-unresponsiveness in living-donor kidney transplantation. Cell-based therapeutic approaches may eventually revolutionize immunosuppression in kidney transplantation in the near future.